INTEREPRETATION DES SIGNES ANNONCIATEURS DES PANNES INFORMATIQUES COURANTES AU DEMARRAGE DES ORDINATEURS A KINDU (Enquête menée à Kindu dans la commune Kasuku de Janvier à octobre 2021) - Albert, OMOKENDE OTSHUDI (IJRDO -Journal of Computer Science Engineering, 2021)
This research which carried on the interpretation of the signs heralding the current data-processing breakdowns to the starting of the computers through a survey carried out in the Kasuku commune to Kindu makes it possible us to understand that these signs are known by the technicians who deal with the maintenance of the computers. Except the beeps with the starting of the computer which are well interpreted by all the surveyed subjects, the other signs are well interpreted, but in different proportions. The starting of the computer but not of Windows and starting of Windows but with problems are the signs which are badly interpreted by the majority of our surveyed.To the various breakdowns with the starting of the computer, tracks of solutions are given through this research in the part devoted to the general considerations (see II).